Iowa Birdline update, March 25, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Notes for the Iowa Birdline update for March 25, 1994. Highlights include Mountain Bluebird, Iceland Gull and Varied Thrush. Epson - sheet feed/flatbed